Lung Histopathology of Laying Hens Infected by Colibacillosis in the Animal Cages Experiments of the Disease Investigation Center 6, Denpasar, Bali - Yanti, Kadek Ayu Trisna; Setyawati, Iriani; Astiti, Ni Putu Adriani (Advances in Tropical Biodiversity and Environmental Sciences; Vol 3 No 2 (2019): ATBES, 2019)
This study aimed to determine the lungs histopathology of laying hens ( Gallus gallus domesticus ) at the Animal Cage Experiments in the Disease Investigation Center 6, Directorate General of Live Stock (DIC-6 DGLS), Denpasar, Bali, which died from colibacillosis infection. Sample of lungs were cut transversely then put into 10% of Neutral Buffer Formalin, then processed histologically by paraffin method and stained with Hematoxylin-Eosin. Observation under microscope (magnification 100x and 400x) was done for histopathological examination. Laying hens died from colibacillosis infection showed that their lungs were infected by colibacillosis, and there were found 62.50% of necrosis, 75% of inflammatory cells infiltration and 80% of hemorrhage in the lungs.